2018
DOI: 10.4103/ijoem.ijoem_168_17
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic health expenditure and impoverishment effects of out-of-pocket expenses: A comparative study of tannery and non-tannery workers of Kanpur, India

Abstract: Purpose:Treatment-seeking behaviors and economic burden because of health expenditure are widely discussed issues in India, and more so in recent times. The aim of this study is to identify health problems of tannery workers and their treatment-seeking behavior and their health expenditure.Data and Methods:The primary data used in this article were collected through a cross-sectional household survey of 284 male tannery workers in the Jajmau area of Kanpur city in the state of Uttar Pradesh, during January–Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Although we found that a higher proportion of households had hospitalization treatment in the study, the mean duration of inpatient care in this study was 4.7 ± 4.6 days, with a median of 3 days, which is markedly lesser than those found by Rout and Choudhary (Odisha, 2018) 16 and Kashyap et al (Kanpur, 2018), 15 likely due to high turnover rate of patients at nearby large tertiary care hospitals. Rout and Choudhary (Odisha, 2018) 16 found the average duration of inpatient care at secondary-level public health institutions in two districts of Odisha to be 6.14 days.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Although we found that a higher proportion of households had hospitalization treatment in the study, the mean duration of inpatient care in this study was 4.7 ± 4.6 days, with a median of 3 days, which is markedly lesser than those found by Rout and Choudhary (Odisha, 2018) 16 and Kashyap et al (Kanpur, 2018), 15 likely due to high turnover rate of patients at nearby large tertiary care hospitals. Rout and Choudhary (Odisha, 2018) 16 found the average duration of inpatient care at secondary-level public health institutions in two districts of Odisha to be 6.14 days.…”
Section: Discussioncontrasting
confidence: 74%
“…Rout and Choudhary (Odisha, 2018) 16 found the average duration of inpatient care at secondary-level public health institutions in two districts of Odisha to be 6.14 days. Similarly, Kashyap et al (Kanpur, 2018) 15 reported, the mean duration of stay for tannery workers to be 18.7 ± 11.9 days.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Next private sector stands out majorly dominated by HHs as FA contributing a massive 79.19% in co-payments. 10.08% OOPE financed by borrowings similarly reported by earlier studies was impacting lifestyle via implicit costs (Bajpai et al, 2017;Haghparast-Bidgoli et al, 2015;Kashyap et al, 2018;Mishra & Mohanty, 2019;Sharma et al, 2002). Indian Government's target of doubling the public health expenditure by 2025 necessitates stronger Health Management Information System (HMIS) tracking.…”
Section: Resultsmentioning
confidence: 89%
“…Likewise, the higher use of patients' savings (37.7%) for healthcare in HIV services in this study was in agreement with what was found in a study where being a patient and a payer for medical bills increased susceptibility to the CHE. People with poor household incomes face more burdens of CHE, which is a hindrance to the attainment of UHC as more households of poor status are further pushed into poverty [ 26 , 27 , 28 , 29 ]. Poverty is both a cause and a consequence of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%